2016
DOI: 10.17577/ijertv5is060219
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Mechanical Properties of Aluminium Hybrid Metal Matrix Composites

Abstract: Aluminium hybrid metal matrix composites have been widely used in automobile, aerospace and structural application because of their good tribological and mechanical properties. This work deals with the preparation of composites and evaluation of mechanical properties by introducing micro size reinforcement particle in the aluminium alloy. The reinforcement of Al alloy hybrid metal matrix composite with Al2O3, B4C, and SiC particles are produced by stir casting. After heat treatment process the casting material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…This composition includes a balanced mix of reinforcements, specifically lower quantities compared to other tested composites, which contributes to higher MRR due to reduced obstruction to the material removal process and lower TWR as there is less abrasive interaction with the tool. Similar findings regarding the influence of reinforcement quantity on machining performance are shown by Nanda Kumar and Kanagaraj [3], who discussed how varying reinforcement levels affect mechanical properties and machining characteristics of metal matrix composites.…”
Section: Influence Of Edm Input Parameters On Materials Removal Rate ...supporting
confidence: 76%
See 1 more Smart Citation
“…This composition includes a balanced mix of reinforcements, specifically lower quantities compared to other tested composites, which contributes to higher MRR due to reduced obstruction to the material removal process and lower TWR as there is less abrasive interaction with the tool. Similar findings regarding the influence of reinforcement quantity on machining performance are shown by Nanda Kumar and Kanagaraj [3], who discussed how varying reinforcement levels affect mechanical properties and machining characteristics of metal matrix composites.…”
Section: Influence Of Edm Input Parameters On Materials Removal Rate ...supporting
confidence: 76%
“…It has also been noted that increasing the number of reinforcements improves MMC mechanical properties, depending on the reinforcement type, or reduces cost without changing properties. Aluminium composites reinforced with silicon carbide and graphite were investigated by Nanda Kumar et al [3]. Aluminium with Silicon Carbide particles (SiC), graphite, and Alumina, solid lubricant, and graphite at solid-state were stir cast to make the composites.…”
Section: Introductionmentioning
confidence: 99%
“…They conducted sliding wear tests on the prepared composite and their test results show that 10 wt % of Al 2 O 3 , 6 wt % of SiC, and 4 wt % of E-glass fibers possess minimum wear as compared with the Al6061 alloy. Basithrahman and Arravind [15] carried out an experimental investigation for determining the mechanical properties of a hybrid Al6061 alloy with the addition of three reinforcement materials, namely SiC (5%), Al 2 O 3 (3% to 12%), and B 4 C (5%). They observed that the composite with the composition of 12% Al 2 O 3 with 5% of SiC and B 4 C exhibits more hardness and they concluded that the hardness of the composite increases with an increase in Al 2 O 3 content.…”
Section: Introductionmentioning
confidence: 99%
“…AlMMCs are particularly essential for a broad variety of applications in industries because of their good mechanical features, low weight, and cost [12]. In the manufacturing of MMC materials, there are a few different production methods that may be used, and AlMMCs can also be created by a few different processes [13]. Different characteristic profiles are attainable, despite the fact that the materials used in the fabrication process are of the same composition and are used in the same quantities [14].…”
Section: Literature Surveymentioning
confidence: 99%